Sequência didática sobre o sistema solar: uma proposta utilizando TDIC nos anos iniciais - Souza, Mariana Coradini de (2022)
This study is linked to the research line Management of Educational Technologies in Network, of the Graduate Program in Educational Technologies in Network in the professional master's modality of the Federal University of Santa Maria. Digital technologies are increasingly present in everyday life, transforming the way people communicate, have fun and study. Traditional approaches to the study of scientific phenomena can become more interesting when supported by digital tools that use technology to aid student learning. Among these forms, the use of educational applications that simulate phenomena and situations, gamification and simulations in augmented reality stands out. Thus, it is in this context that the general objective of this work is situated: to analyze how digital information and communication technologies can contribute to the teaching and learning of students in the fifth year of elementary school through the development and implementation of a didactic sequence about the Solar System. For the development of this work, a didactic sequence was created as a product in order to evaluate the contribution of digital information and communication technologies in the teaching and learning process of students. This is an applied research, with a quali-quantitative approach, with a descriptive objective via simple observation. The instruments for data collection were through an initial questionnaire (pre-test), observations, field diary, photographic records, final questionnaire (post-test) and evaluative questionnaire of activities with the teachers. To analyze the data, the steps were followed using the procedures provided by Bardin (2016): pre-analysis, material exploration and treatment of results, inference and interpretation. Four categories of analysis of the results were established, namely: motivation, collaboration, mediation and active learning. According to the analysis of the results, it was observed a satisfactory involvement of the students in the activities and a greater motivation for the study of the content and when comparing the data it is observed a significant increase of correct answers, considering that the average percentage of correct answers rose from 33 .2% in the pre-test to 58% in the post-test and when performing the paired t test we obtained a statistically significant average increase per student of 3.0 correct answers in the post-test, with 81.6% increasing the score suggesting that the digital technologies used in the didactic sequence have the potential to help in the teaching and learning processes in basic education.